Studi Keamanan Pangan Kimiawi dari Logam Berat Timbal pada Euthynnus Sp , di Perairan Semarang. - Widajanti, Laksmi; Girsang, Rohdearni; Pradigdo, Siti Fatimah (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2004)
ABSTRACT Background: One of the impact of industrial development is the decreasing water quality that may cause pollution of living resources,especially the fish. The objective of this research is to determine the consentration of lead (Pb) Euthynnus sp. and to analize its chemical safety in the coast Semarang. Methods: This study is a descriptif research with a cross sectional approach. The 30 samples of Euthynnus was taken from the markets in Semarang City, including Jatingaleh, Peterongan, Bulu, Johar, dan Rejomulyo market. Results: The finding of this research showed that the highest Lead consentration in Euthynnus Sp was 2,51 ppm and the lowest was 0 ppm with the average of 0,81 ppm and the standard deviation was 0,91 ppm. There was 33,3 % sample which has the concentration of Lead more than the maximum standard. Conclusion: It was suggested to choose the fresh fish to consumed by considering the site of fish catching. It is also suggested to the government and the related institution in semarang City to make a regulation and policy to protect the consumer from the toxic effect of heavy metal in fish. Key word : Euthynnus sp., heavy metal (Lead), Coast of Semarang